The Need for National Registry - Yoga Yuniadi (The Indonesian Heart Association, 2014)
Currently medical outcomes research has generally been conducted with 3 sources of data: randomized clinical trials, administrative claims databases, and data registries. Each of these data sources has a unique set of applications, data quality issues, and requirements.1 In United State, clinical trials is part of the pharmaceutical and device pre-approval process thus it has highly regulated requirements for source document verification.2 In contrast, quality control of administrative data is primarily limited to fields directly related to claims adjudication. Thus, administrative claims data are significantly limited for the purposes of performing healthcare research.3 Like administrative claims data, registries are nonrandomized, observational datasets that can be generalized to real-world practice, depending on the representativeness of participants and the completeness of enrollment.4 However, as with the data collected in randomized clinical trials, registries include detailed clinical data using standardized data definitions.